Do Functional Movement Screens Predict Body Composition Changes after Resistance Training? - Rosenberg, Jared; Natarajan, Jytosna; Carenter, David J; Peluso, Chris; Hilton, Christie; Champ, Colin E. (Sports Medicine International Open, 2025)
Although the function movement screen (FMS) has been widely used in the general population, no study to date has used the FMS as a preparticipation screen for individuals with breast cancer (BC) engaging in an exercise regimen. Even though individuals with BC are anthropometrically similar to individuals without cancer, the lack of studies assessing the FMS in individuals with BC may potentially hinder exercise prescription. Therefore, we aim to examine the relationships of the FMS score to anthropometric biomarkers in individuals with BC before undergoing an exercise regimen. One-hundred and twelve women with BC underwent a thrice-weekly three-month dose-escalated exercise regimen utilizing multi-joint compound movements and linear progression balanced with resistance training volume to elicit hypertrophy. FMS score and anthropometric markers were assessed pre- and post-intervention. With significance set at p≤0.05, baseline FMS scores correlated significantly with all anthropometric markers, and was similar to previous studies published in non-cancer populations. However, baseline FMS scores were not associated with changes in anthropometric markers, from pre- to post-intervention. While the baseline FMS score was not associated with changes in anthropometric markers, the similar correlation found in our study compared to previous studies suggest that the FMS can be used as a preparticipation in individuals with BC to help guide the exercise regimen. Future studies designed to elicit weight loss in individuals with BC should assess whether the baseline FMS score is predictive of anthropometric changes.
Keywords: functional movement screen; resistance training; breast cancer